1986
DOI: 10.3382/ps.0652226
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Feed Restriction on Growth, Body Composition, and Egg Production of Broiler Females Through 68 Weeks of Age

Abstract: Effects of ad libitum and restricted (50% of ad libitum) feeding on performance of female broilers were assessed in a 68-week experiment. The treatments imposed were AA, fed ad libitum throughout; RR, fed restricted amounts of feed throughout; RA restricted through 24 weeks of age and ad libitum thereafter; and AR, fed ad libitum through 24 weeks and restricted thereafter. Average age at first egg was delayed by 17 days in RA hens compared with AA hens. Average body weight at first egg was 3.9 kg for RA birds … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
11
2

Year Published

1988
1988
2004
2004

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 7 publications
5
11
2
Order By: Relevance
“…Katanbaf et al (1989a) suggested that body weight in ad-libitum-fed birds may reach a plateau as a consequence ofreduced voluntary food intake due to a loss in "vigor". The poor laying performance of the adIibitum-fed hens compared to the feedrestricted hens supports the findings of previous studies (Robbins et al 1986;Hocking et al 1987Hocking et al , 1989Katanbaf et al 1989b) and reinforces the necessity of limiting feed intake of broiler mothers. It has been reported previously that ad libitum feeding hastens sexual maturity, due to the fact that such birds attain the prerequisite body mass and body composition sooner than feedresrricted hens (Brody et al 1980;Robbins et al 1986;Ingram and Wilson 1987;Hocking et al 1989;Katanbafet al 1989b).…”
Section: Resultssupporting
confidence: 80%
See 2 more Smart Citations
“…Katanbaf et al (1989a) suggested that body weight in ad-libitum-fed birds may reach a plateau as a consequence ofreduced voluntary food intake due to a loss in "vigor". The poor laying performance of the adIibitum-fed hens compared to the feedrestricted hens supports the findings of previous studies (Robbins et al 1986;Hocking et al 1987Hocking et al , 1989Katanbaf et al 1989b) and reinforces the necessity of limiting feed intake of broiler mothers. It has been reported previously that ad libitum feeding hastens sexual maturity, due to the fact that such birds attain the prerequisite body mass and body composition sooner than feedresrricted hens (Brody et al 1980;Robbins et al 1986;Ingram and Wilson 1987;Hocking et al 1989;Katanbafet al 1989b).…”
Section: Resultssupporting
confidence: 80%
“…Furthermore, Katanbaf et al (1989b) reported Katanbaf et al 1989a) but differs from the work of Robbins et al (1986) who reported similar mortality figures for hens which were feed-restricted or ad-libitumfed during lay.…”
Section: Resultscontrasting
confidence: 45%
See 1 more Smart Citation
“…Age at sexual maturity, days from photostimulation to sexual maturity, and settable egg age data indicate that HIGH birds were able to respond to the photostimulatory cue more quickly than the LOW or STD birds (Table 2). Previous studies have shown that increasing BW during rearing advances age at sexual maturity in broiler breeder hens (Robbins et al 1986, Yu et al 1992, Yuan et al 1994. However, the differences in BW targets between rearing growth curves used in the current study were smaller than that of the previous studies.…”
Section: Body Weight and Sexual Maturitycontrasting
confidence: 55%
“…Feed restriction delays age at sexual maturity (Robbins et al 1986;Yu et al 1992) possibly through delaying maturation of the hypothalamic-anterior pituitary axis (Yu et al 1992), by later attainment of adequate body size (Brody et al 1980;Dunnington et al 1984), or by delaying the achievement of a favorable metabolic environment (Renema et al 1999a) to commence sexual maturation. The effects of small differences in feed restriction programs or in photostimulation ages have also been investigated.…”
mentioning
confidence: 99%